Isotopic identification of photofissed nuclear materials in stainless steel containers using delayed gamma-rays - Pylypchynets, I.V.; Parlag, O.O.; Maslyuk, V.T.; Oleynikov, E.V.; Lengyel, A.I. (Problems of Atomic Science and Technology, 2022)
The results of isotope identification of nuclear materials (²³²Th, ²³⁵U, ²³⁸U, ²³⁹Pu) packed in hermetic stainless steel containers by their stimulated delayed gamma radiation are presented. The ratios of the values of the time dependences of the intensity of gamma radiation of the light and heavy product of their photofission were used for the analysis. Gamma radiation from photofission products ⁸⁹Rb (1031.9; 1248.1 keV) and ¹³⁸Cs (1009.8; 1436.8; 2218.0; 2639.6 keV) was used to differentiate nuclear materials. The photofission reaction the samples of nuclear materials was stimulated on an electron accelerator, an M-30 microtron, at maximum bremsstrahlung energy of 12.5 MeV. The possibility of carrying out isotopic identification of nuclear materials using 8 ratios of the yields of first members of decay chain of ⁸⁹Rb light fission product to correspondence values of ¹³⁸Cs heavy fission product has been demonstrated. Представлено результати ізотопної ідентифікації ядерних матеріалів (²³²Th, ²³⁵U, ²³⁸U, ²³⁹Pu), упакованих у герметичні контейнери з нержавіючої сталі, за їх стимульованим затриманим гамма-випромінюванням. Для аналізу використовувалося відношення значень часових залежностей інтенсивності гамма-випромінювання від легкого та важкого продуктів їхнього фотоподілу. Гамма-випромінювання продуктів фотоподілу ⁸⁹Rb (1031,9; 1248,1 кеВ) та ¹³⁸Cs (1009,8; 1436,8; 2218,0; 2639,6 кеВ) використовувалися для диференціації ядерних матеріалів. Стимуляція реакції фотоподілу зразків проводилася на електронному прискорювачі – мікротроні М-30 з максимальної енергії гальмівного випромінювання 12,5 МеВ. Продемонстровано можливість проведення ізотопної ідентифікації ядерних матеріалів за 8 відношеннями виходів перших членів ланцюжка легкого продукту ⁸⁹Rb до окремих значень важкого продукту ¹³⁸Cs.